Intervenções assistidas por animais: diálogos sobre animais coterapeutas, bem-estar animal e clínica de orientação fenomenológica - REINERT, Ana Paula Rezzo Pires (2020)
The main objective of this study is a phenomenology of scientific literature published from 2014 to 2019, presenting therapeutic and psychotherapeutic evidence of the participation of non-human animals as co-therapists, in the practices of Animal Assisted Interventions (AAI). It also questions the speciesism and objectification of the animal in the practices accessed, showing the binomial man-animal in different contexts of professional practice. The methodological approach used was the phenomenological attitude and method of scientific production on AAIs. 35 studies were selected and analyzed phenomenologically, specifically the stages of epoché and eidetic reduction, according to the categories: type of intervention, co therapist species, study subjects, design, phenomenon and reference to animal welfare. The phenomenological attitude and method allowed (dis)covering and criticizing how IAAs are used, including Animal Assisted Therapies, as well as allowing a critical reading of the collected data. Among the results systematized and analyzed phenomenologically, we highlight the significant increase in scientific publications on IAAs, the prevalence of studies with dogs as co-therapists and investigations carried out by psychologists. At the end, benefits, risks, limits and suggestions from other research in the field of IAAs were presented. From this study, which used 35 scientific articles from the platforms: BVS, PePsic and Pubmed, it was observed that the contact between man and animal shows significant improvements in the patient general condition. The studies reveal a greater interest in dog co-therapists and the child audience as being more benefited in human-animal interactions. Issues related to concern for animal welfare are still little discussed.